Synthesis of some pyrimidine derivatives from-4- acetyl pyridine - Reem. S. Najem (Tikrit Journal of Pure Science)
Chalcones compounds(1-4) were prepared from - 4 - acetyl pyridine with different aromatic aldehyde benzaldehyde in the presence of KOH  solution .